2008
DOI: 10.3892/ijmm.21.5.593
|View full text |Cite
|
Sign up to set email alerts
|

Steroidogenic acute regulatory protein gene expression, steroid-hormone secretion and proliferative activity of adrenocortical cells in the presence of proteasome inhibitors: In vivo studies on the regenerating rat adrenal cortex

Abstract: Abstract.Previous studies have shown that proteasome inhibitors promote the accumulation of steroidogenic acute regulatory protein (StAR) in cultured rat adrenocortical cells. Unexpectedly, this response was associated with a moderate lowering in the corticosterone secretion and proliferation rate of cultured cells. Hence, we studied the effects of proteasome inhibitors MG115 and MG132 on the secretion and proliferative activity of the regenerating adrenal cortex in rats 5 days after surgery. Animals were give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…This protein is responsible for the transport of cholesterol from the outer to the inner mitochondrial membrane. An earlier study revealed notable downregulation of both StAR gene and protein expression levels in regenerating rat adrenals on experimental day 5 (31). The current study confirmed these data and revealed a significant upregulation in gene expression between experimental days 8-15.…”
Section: Discussionsupporting
confidence: 89%
“…This protein is responsible for the transport of cholesterol from the outer to the inner mitochondrial membrane. An earlier study revealed notable downregulation of both StAR gene and protein expression levels in regenerating rat adrenals on experimental day 5 (31). The current study confirmed these data and revealed a significant upregulation in gene expression between experimental days 8-15.…”
Section: Discussionsupporting
confidence: 89%
“…This protein is responsible for the transport of cholesterol from the outer to the inner mitochondrial membrane ( 53 ). Earlier immunohistochemical and immunofluorescence studies have revealed the presence of Star protein in both the ZG and ZF/R of the rat adrenal cortex ( 54 57 ). In the mouse adrenal glands, Star mRNA levels (assessed by RT-PCR) have been reported be slightly higher in males than in females, although the differences were not statistically significant ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…QPCR was performed by means of the Lightcycler 2.0 instrument (Roche) with the 4.05 software version. SYBR green detection system was applied as described earlier [30,31,[38][39][40]. Every of 20 µL reaction mixtures contained 2 µL template cDNA (standard or control), 0.5 µM of specific primer and a 3.5 µM MgCl 2 .…”
Section: Reverse Transcription Reverse Transcription With Oligodt Prmentioning
confidence: 99%